Brand Building and Management in The Polycarbonate Sheet Industry in Southeast Asia: Execution and Effects of Business Management Strategies - Zhang, Jianxu; Zhang, Jing (International Journal of Accounting and Economics Studies, 2025)
This paper has discussed the effect that brand-building and management practices have in business performance in the polycarbonate sheet businesses in Southeast Asia. The primary objective was to understand how the industrial brands grow and implement proper branding strategies in the multiregional markets. The study followed a secondary data approach where information was recorded on industry reports, scholarly articles, and market studies. This was one way of doing a thorough analysis of the branding trends in the region, consumer choices, and business performance. Major findings indicated that the quality of brands plays a crucial role in influencing industrial purchasing activities, as well as personalising business options like local affiliations and provision of technical assistance, increases brand confidence. Differences exist regionally, and the executions in branding processes will have to be adaptive, and great brand management was reported to boost customer loyalty and market expansion. Some of the challenges are the differences in regulations, differences in branding practices, and logistics. On the whole, the paper came to the conclusion that region-specific and well-planned branding methods would play a crucial role in long-term growth and customer retention within this competitive B2B industrial environment.